EDUCATIONAL LEVEL AND REPRODUCTIVE HEALTH OF RURAL WOMEN IN NOTHERN CROSS RIVER STATE, NIGERIA - LAZARUS BASSEY ABONOR; ESTHER E-C UZOH; PHILOMINA UGBE AMOKEYE; JOSEPH EDUM TAKWAN (International Studies Journal)
This study investigated educational level and reproductive health of rural women in Northern Cross River State, Nigeria. It explored how educational level influence reproductive health outcomes. The study identified key challenges faced by rural women to include limited educational opportunities, inadequate family planning services, unsafe abortions, untreated sexually transmitted infections (STIs), poor prenatal and postnatal care, and barriers to cervical cancer screening. These challenges are compounded by economic instability, poor healthcare infrastructure, educational gaps, religious barriers, and traditional norms related to early childbearing. Utilizing a cross-sectional research design, the study targeted women of reproductive age (18-54 years) across the five Local Government Areas in the northern Cross River State. A sample size of 400 respondents were used. Quantitative data were collected through structured questionnaires and analyzed using descriptive statistics and Pearson Product Moment correlation Coefficient. Qualitative insights were gained through Key Informant Interviews (KIl) with healthcare professionals, community leaders, and local stakeholders, and were analyzed thematically. The study was theoretically guided by the Health Belief Model, to understand how educational level influence reproductive health decisions. Findings revealed significant relationships between education level with reproductive health outcomes. Higher educational attainment is associated with improved reproductive health, while living in rural areas. Based on the findings, the study recommends targeted interventions, including expanded educational opportunities, improved healthcare infrastructure, economic empowerment initiatives, community-based programmes promoting delayed marriage, family planning, and Social Workers advocacy for policies that can address these challenges, ensuring that interventions are tailored to the unique needs of rural women.